PENGARUH INVESTASI TERHADAP JUMLAH PENDUDUK MISKIN DENGAN PRODUK DOMESTIK REGIONAL BRUTO SEBAGAI VARIABEL INTERVENING - Situmorang, Frandika; Syahbana, Eza; Alisya, Jeane; Naibaho, Angelina Rolas Olivia; Marbun, Jonatan; Siregar, Filja Azkiah; Suharianto, Joko (STIE Jambatan Bulan, 2025)
Poverty is a complex issue and challenge for developing countries because it can cause various social problems such as an increase in the number of homeless people, prostitutes, and street children. North Sumatra is one of the provinces in Indonesia with the largest GRDP outside Java. However, the number of poor people in North Sumatra still fluctuates every year. This study aims to analyze the effect of investment on the number of poor people in North Sumatra Province with Gross Regional Domestic Product (GRDP) as an intervening variable. This study uses the path analysis method to explore the causal relationship between investment, GRDP, and the number of poor people with secondary data for the period 2002-2023. The variables analyzed include Domestic Investment (PMDN), Foreign Investment (PMA) as investment, and GRDP and the number of poor people. The analysis was carried out through classical assumption tests, including normality tests, autocorrelation, multicollinearity, and heteroscedasticity, as well as partial significance testing (t-test) to assess the effect of each variable